It's already there - Tomczyk, Zofia Blanka, 1993- (2019)
It’s already there” by Zofia Tomczyk is the graduation work from the Department of Performing Arts at Iceland University of the Arts. Concept, performance, music, lights: Zofia Tomczyk Mentorship: Bonnie Buckner Thanks for artistic advice: Michikazu Matsune, Satu Herrala, Alexander Roberts, Kate McIntosh, Steinunn Ketilsdóttir Duration: 40 minutes Premiere: Celestial Bodies Festival / Reykjavik, Iceland Photo: Maciej Zakrzewski Technical assistance: Aron Martin Ásgerðarson It’s already there is a listening practice framed into a performance. This is a practice that takes us into subtleties, tremors, micro-gestures, tiny noises, silence, shifts and stillness. The work is about other modes of giving space to things and through doing so being with oneself and one’s environments in ways that otherwise wouldn’t be available. Project supported by "Młoda Polska" scholarship program of Ministry of Culture and National Heritage in Poland (2019).